A comparative study of open, laparoscopic and robotic partial nephrectomy in obese patients - Webb, Clairese M. (Urol Ann, 2015)
OBJECTIVES: Partial nephrectomy is a standard intervention for the treatment of small renal tumors. Our study compares the outcomes of three different partial nephrectomy methods (open, laparoscopic and robotic assisted) in obese (≥30 Kg/m(2)) patients with renal tumors. MATERIALS AND METHODS: Between 2005-2011, 66 obese patients had partial nephrectomy. Patients were divided into three groups according to intervention received: Open (n = 21), laparoscopic (n = 31) and robotic (n = 14). The outcome variables of blood loss, length of hospital stay, and complications were assessed. RESULTS: Mean blood loss in the laparoscopic group (100 mls) was significantly less than open group (300 mls) and no difference between laparoscopic and robotic groups (150 mls). We observed a shorter median hospital stay in the laparoscopic group (two days) than open group (four days) and no difference between laparoscopic and robotic groups (three days). Three patients in the laparoscopic group had complications: Two grade II and one with grade III (based on Clavien-Dindo classification). Tumor location, pathology, grade, stage, patient gender, age, preoperative creatinine and postoperative creatinine were not different among the groups (P > 0.05). The mean tumor size in the laparoscopic group (2.70 cms) was significantly smaller than that of the open group (4.22 cm) (P < 0.05), but not statistically different from that of the robotic group (2.99 cm). CONCLUSIONS: Our study demonstrates that in obese patients, both laparoscopic and robotic partial nephrectomy are associated with less blood loss than open partial nephrectomy. Second, the length of the hospital stay was not related to the type of utilized intervention.